Ответы и объяснения

2013-07-13T16:55:57+00:00

\sqrt{\frac{9 \sqrt {18} - \sqrt 3}{\sqrt {18} - \sqrt 3}+\sqrt 6}- \sqrt {(6 \sqrt 3 - 10)}^2 =

 

\sqrt{\frac{9 \sqrt {18} - \sqrt 3}{\sqrt {18} - \sqrt 3}+\sqrt 6}- {(6 \sqrt 3 - 10)} =

 

\sqrt{\frac{(9 \sqrt {18} - \sqrt 3)(\sqrt {18} +\sqrt 3)}{(\sqrt {18} - \sqrt 3)(\sqrt {18} + \sqrt 3)}+\sqrt 6}- {(6 \sqrt 3 - 10)} =

 

\sqrt{\frac{9 \cdot{18} + 9 \sqrt{18} \cdot \sqrt 3 - \sqrt 3 \cdot \sqrt {18} - 3}{ {18} - 3}+\sqrt 6}- {(6 \sqrt 3 - 10)} =

 

\sqrt{\frac{162 + 27 \sqrt{6} - 3 \sqrt {6} - 3}{ 15}+\sqrt 6}- {(6 \sqrt 3 - 10)} =

 

\sqrt{\frac{159 + 24 \sqrt{6} }{ 15}+\sqrt 6}- {(6 \sqrt 3 - 10)} =

 

\sqrt{\frac{53 + 8 \sqrt{6} }{ 5}+\sqrt 6}- {(6 \sqrt 3 - 10)} =

 

\sqrt{\frac{53 + 8 \sqrt{6} }{ 5}+ \frac{5\sqrt 6}{5}}- {(6 \sqrt 3 - 10)} =

 

\sqrt{\frac{53 + 13 \sqrt{6} }{ 5}}- {(6 \sqrt 3 - 10)} \approx 3,7270001

 

после самой простой формы  подал  апроксимующе число,